7. Penyebab Jepang Melakukan Penangkapan Paus di Antartika - I Gusti Krishna Aditama; Reni Windiani; Nadia Farabi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
The aim of this research is to find out why Japan still continue their whaling program, even though the previous program was banned. Moratorium of whaling for commercial purpose was signed in 1986 by member states of International Whaling Commission. The next year after the moratorium, Japan launched scientific research program named Japanese Whale Research Program under Special Permit in the Antarctic (JARPA). The second research program which is named JARPA II was banned by International Court of Justice due to violations of some articles on International Convention for Regulation of Whaling. After the banned, Japan is back on doing scientific whaling program. This research is done by using explanatory method, using qualitative analysis technique through accumulating primary and secondary data. Based on green political theory, environmental security, and ecological crime, the main reason why Japan still continue their whale research program is culture. This culture starts to disappear when whaling moratorium was signed. Government of Japan created several policies to address this issue. Supports Institute of Cetacean research for whale research and launched campaign activities to reintroduce whale culture for the people. These evidence proof that culture is the main motive on why Japan still continue their whale research program.